MS Lesions Are Better Detected with 3D T1 Gradient-Echo Than with 2D T1 Spin-Echo Gadolinium-Enhanced Imaging at 3T - Crombé, A.; Saranathan, M.; Ruet, A.; Durieux, M.; de Roquefeuil, E.; Ouallet, J.C.; Brochet, B.; Dousset, V.; Tourdias, T. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: In multiple sclerosis, gadolinium enhancement is used to classify lesions as active. Regarding the need for a standardized and accurate method for detection of multiple sclerosis activity, we compared 2D-spin-echo with 3D-gradient-echo T1WI for the detection of gadolinium-enhancing MS lesions. MATERIALS AND METHODS: Fifty-eight patients with MS were prospectively imaged at 3T by using both 2D-spin-echo and 3D-gradient recalled-echo T1WI in random order after the injection of gadolinium. Blinded and independent evaluation was performed by a junior and a senior reader to count gadolinium-enhancing lesions and to characterize their location, size, pattern of enhancement, and the relative contrast between enhancing lesions and the adjacent white matter. Finally, the SNR and relative contrast of gadolinium-enhancing lesions were computed for both sequences by using simulations. RESULTS: Significantly more gadolinium-enhancing lesions were reported on 3D-gradient recalled-echo than on 2D-spin-echo (n = 59 versus n = 30 for the junior reader, P = .021; n = 77 versus n = 61 for the senior reader, P = .017). The difference between the 2 readers was significant on 2D-spin-echo (P = .044), for which images were less reproducible (κ = 0.51) than for 3D-gradient recalled-echo (κ = 0.65). Further comparisons showed that there were statistically more small lesions (<5 mm) on 3D-gradient recalled-echo than on 2D-spin-echo (P = .04), while other features were similar. Theoretic results from simulations predicted SNR and lesion contrast for 3D-gradient recalled-echo to be better than for 2D-spin-echo for visualization of small enhancing lesions and were, therefore, consistent with clinical observations. CONCLUSIONS: At 3T, 3D-gradient recalled-echo provides a higher detection rate of gadolinium-enhancing lesions, especially those with smaller size, with a better reproducibility; this finding suggests using 3D-gradient recalled-echo to detect MS activity, with potential impact in initiation, monitoring, and optimization of therapy. FSPGRfast-spoiled gradient recalledGREgradient recalled-echoSEspin-echo